An overview of pesticide management in Nepal - Adhikari, Parashu Ram (Journal of Agriculture and Environment, 2018)
Agriculture is a wider sector where 54% people are engaged and one-third GDP contributed to the nation. Due to diverse climatic regions, farmers grow different types of agricultural commodities and presence of different pests reduces their production and thus need to apply pesticides. Pesticide Registration and Management Division under the Department of Agriculture is a legal authority to register as well as restrict or ban certain pesticides used in the agricultural sector in Nepal. The paper also emphasizes how Nepal has doing pesticide reduction for the pest management in agriculture considering the food safety, animal and human health and environment protection. And it also focuses on the legal aspects on pesticide management and status of registered, restricted and banned pesticides in the context of neighboring countries and addresses to fulfill the obligations of the international convention related to pesticides and industrial chemicals.